Illness Severity Moderated Association Between Trait Anxiety and Amygdala-Based Functional Connectivity in Generalized Anxiety Disorder - Du, Yang; Li, Hailong; Xiao, Hongqi; Wang, Mei; Zhang, Wei; Gong, Qiyong; Qiu, Changjian; Huang, Xiaoqi (Frontiers in Behavioral Neuroscience, 2021)
Trait anxiety is considered a vulnerability factor to develop generalized anxiety disorder (GAD). The amygdala is related to both trait anxiety and GAD. Thus, we investigated amygdala-based functional connectivity (FC) in drug-naive non-comorbid GAD patients and explored their associations with personality, symptoms, and illness severity. FC analyses using bilateral amygdala as seeds were performed with resting-state functional MRI data from 38 GAD patients and 20 matched healthy controls (HCs). Clinical characteristics were correlated with FC Z-scores from regions showing significant group differences. Furthermore, moderation analyses were used to explore the conditional effect of illness severity, measured by the Clinical Global Impression-Severity scale (CGI-S), on the FC and trait anxiety relationship. Relative to HCs, GAD patients showed hypoconnectivity between the amygdala and rostral anterior cingulate cortex (rACC), inferior frontal gyrus (IFG), parahippocampal gyrus and cerebellum and hyperconnectivity between the amygdala and superior temporal gyrus (STG), insula, and postcentral gyrus. In GAD patients, there were negative associations between amygdala-rACC connectivity and symptom severity and trait anxiety and positive associations between amygdala-IFG connectivity and symptom severity. Moreover, CGI-S score moderated the negative correlation between trait anxiety and amygdala-rACC FC. We demonstrated that there is extensive amygdala-based network dysfunction in patients with GAD. More importantly, amygdala-rACC connectivity played a key role in the neural pathology of trait anxiety. Finally, the more severe the illness severity was, the stronger the negative association between trait anxiety and amygdala-rACC FC. Our results emphasize the importance of personalized intervention in GAD.